Analisis Kebutuhan dan Kualitas Air Bersih Tupapa di Desa Sumeith Pasinaro Kecamatan Elpaputih Kabupaten Seram Bagian Barat - Feronika Pulamajen; Ferdinand Salomo Leuwol; Mohammad Amin Lasaiba (Jurnal Pendidikan Geografi Unpatti, 2025)
This study is grounded in the growing challenges of clean water management in small island regions, where ecological degradation and limited sanitation infrastructure threaten community health. Although water availability in Sumeith Pasinaro Village remains sufficient, its quality does not meet health standards, particularly in microbiological aspects. The study aims to analyze the relationship between household water demand and water quality while identifying social, ecological, and institutional factors influencing water sustainability. Using a qualitative case study approach, data were collected through field observations, in-depth interviews, and laboratory analysis from two sampling points at the Tupapa water source. The findings indicate that microbiological contamination results from poor sanitation awareness, degradation of catchment vegetation, and the absence of proper water treatment systems. Conversely, the physical and chemical quality remains acceptable. The study contributes to developing a community-based water management framework that integrates ecological conservation, sanitation education, and indigenous cultural values. These insights advance the theoretical understanding of socio-hydrological resilience in island contexts.